Genomic Imprinting at the Porcine PLAGL1 Locus and the Orthologous Locus in the Human - Ahn, Jinsoo (Genes (Basel), 2021)
Implementation of genomic imprinting in mammals often results in cis-acting silencing of a gene cluster and monoallelic expression, which are important for mammalian growth and function. Compared with widely documented imprinting status in humans and mice, current understanding of genomic imprinting in pigs is relatively limited. The objectives of this study were to identify DNA methylation status and allelic expression of alternative spliced isoforms at the porcine PLAGL1 locus and assess the conservation of the locus compared to the orthologous human locus. DNA methylome and transcriptome were constructed using porcine parthenogenetic or biparental control embryos. Using methylome, differentially methylated regions between those embryos were identified. Alternative splicing was identified by differential splicing analysis, and monoallelic expression was examined using single nucleotide polymorphism sites. Moreover, topological boundary regions were identified by analyzing CTCF binding sites and compared with the boundary of human orthologous locus. As a result, it was revealed that the monoallelic expression of the PLAGL1 gene in porcine embryos via genomic imprinting was maintained in the adult stage. The porcine PLAGL1 locus was largely conserved in regard to maternal hypermethylation, tissue distribution of mRNA expression, monoallelic expression, and biallelic CTCF-binding, with exceptions on transcript isoforms produced by alternative splicing instead of alternative promoter usage. These findings laid the groundwork for comparative studies on the imprinted PLAGL1 gene and related regulatory mechanisms across species.